Control of ultrafast laser ablation efficiency by stress confinement due to strong electron localization in high-entropy alloys - Redka, David; Winter, Jan; Gadelmeier, Christian; Djuranovic, Alexander; Glatzel, Uwe; Minár, Ján; Huber, Heinz Paul (Applied Surface Science, 2022)
In the context of current state of the art, understanding the laser ablation efficiency decrease for pulse durations exceeding the mechanical relaxation time of a few ps remains a pending research question. A heuristic approach may be used to reveal the role of effective penetration depth on ablation efficiency. Extending familiar contributions of this quantity by a term related to the mechanical surface expansion during pulse irradiation, the relation of ablation efficiency and pulse duration is deciphered. Thus, longer pulses are coupled into an expanded surface, revealing a direct link to the violation of stress confinement. To best demonstrate this hypothesis, a material with high electron–phonon coupling as well as low thermal conductivity, i.e., strong electron localization, is required. These properties are accomplished by high-entropy alloys, and the CrMnFeCoNi alloy serves as prime candidate. We report on single-pulse ablation efficiency experiments of the CrMnFeCoNi alloy which are support by our proposed model.
CRIS-Team Scopus Importer:2022-05-20
Keywords: Ablation efficiency; CrMnFeCoNi; High-entropy alloy; Pulse duration; Stress confinement; Ultrafast laser ablation

Dynamics of supported ultrathin molybdenum films driven by strong short laser impact - Khokhlov, V. A.; Petrov, Yu V.; Inogamov, N. A.; Migdal, K. P.; Winter, Jan; Aichele, C.; Rapp, Stephan; Huber, H. P. (Journal of Physics: Conference Series, 2019)
We consider expansion, break off, and flight of 10 nm molybdenum film deposited onto glass support. These events are initiated by action of subpicosecond laser pulse onto film. Approximations for two-temperature equation of state and electron-ion coupling parameter are developed. Heat conduction is unimportant because film is ultrathin and because radius of a laser beam is rather large ∼ 10 μm (thus lateral thermal spreading is insignificant at the considered time scale). We use two-temperature one-dimensional hydrodynamic code to follow evolution of laser induced flow. Additional code for treating transmission and reflection of a monochromatic electromagnetic wave is developed. It is applied to describe interference between transmitted and reflected waves in the layered structure appearing thanks to laser induced expansion and separation of a film.
CRIS-Team Scopus Importer:2019-05-17

Influence of pulse duration and separation on ultrafast single pulse laser ablation in industrial bulk metals: Complete time-resolved surface dynamics and its implications to laser material processing - Winter, Jan; Spellauge, Maximilian; Gies, Philipp; Hermann, Jens; Schmidt, Michael; Huber, Heinz Paul (Proc. SPIE 11267, Laser Applications in Microelectronic and Optoelectronic Manufacturing (LAMOM) XXV, 2020)
The pulse duration dependence and inter pulse separation of pulse sequences influence on the energy specific ablation volume are still today open questions in laser material processing. The complete timescales for the processes involved in laser ablation can be visualized from the initial pulse absorption to the material removal occurring on a microsecond time scale by using an pump-probe microscopy method. Here we present time-resolved and energetic studies of the surface dynamics of the laser ablation processes on aluminium, copper and stainless steel bulk materials, which were analysed for pulse durations ranging from 500 fs to 20 ps, while keeping all other laser parameters constant. Our results indicate that the ablation process should be initiated by pulse durations shorter than the mechanical relaxation time of 3 ps and remain uninterrupted until the final state is reached after about 1 µs.<br

Sub-picosecond single-pulse laser ablation of the CrMnFeCoNi high entropy alloy and comparison to stainless steel AISI 304 - Redka, D.; Gadelmeier, C.; Winter, Jan; Spellauge, M.; Eulenkamp, C.; Calta, P.; Glatzel, U.; Minár, J.; Huber, H. P. (Applied Surface Science, 2021)
In recent years, high entropy alloy research has experienced increased interest and it was found that some of these materials have extraordinary properties. High entropy alloys also show an increased damage resistance to high-energy particle irradiation, mainly due to effects caused by the increased configuration entropy. So far, no detailed studies have been carried out regarding the interaction with high-energy electromagnetic radiation, particularly by means of lasers. In this work, we compare results of ultrashort-pulse laser-matter interaction of the CrMnFeCoNi alloy (Cantor alloy), the most researched representative of this material group, with the conventional alloy stainless steel AISI 304. Since metals can in general be processed efficiently with ultrashort pulses, which is of particular interest for industrial applications, we performed our experiments with single infrared sub-picosecond pulses. The crater surface morphology and process energetics are discussed in detail and the validity of established ablation models is investigated. We find that the damage threshold of the CrMnFeCoNi alloy is slightly lower than that of AISI 304 and consequently CrMnFeCoNi alloy shows an increased ablation volume. Therefore, the high entropy alloy CrMnFeCoNi can be processed efficiently with ultrashort-pulse lasers.
CRIS-Team Scopus Importer:2021-01-22
Keywords: High entropy alloy; Laser ablation; Single-pulse; Stainless steel; Threshold fluence; Ultrashort-pulse

Ultrafast pump-probe ellipsometry and microscopy reveal the surface dynamics of femtosecond laser ablation of aluminium and stainless steel - Winter, Jan; Rapp, Stephan; Spellauge, Maximilian; Eulenkamp, Constanze; Schmidt, Michael; Huber, Heinz P. (Applied Surface Science, 2020)
An ultra-short laser pulse irradiated surface passes through a sequence of physical processes that occur over a wide temporal range, from femtoseconds to microseconds. In this paper for the first time, the complete laser ablation process for industrially relevant metals, aluminium (Al) and stainless steel (AISI 304) is tracked from the initial pulse impact to the final state. Time-resolved surface analytical techniques provide a complementary description of the surface dynamics. The pump-probe ellipsometry reveals changes of the complex refractive index for the first tens of picoseconds and time-resolved microscopy of the irradiated surface gives access to changes of the relative reflectivity from the initial femtosecond pulse impact to the final state at 10 μs. The changes in optical indices are affected by an ultrafast decrease in the density of the surface within the pressure unloading process in the first picoseconds and reveal spallation as the dominant mechanism for laser ablation in Al and stainless steel. The study also implies that the ablation volume is kept at an optimum when the ablation is initiated with ultrafast pulses within the pressure unloading process and is able to evolve over eight orders of magnitude without external perturbations.
CRIS-Team Scopus Importer:2020-02-18
Keywords: Laser ablation; Nanostructure; Pump-probe reflectometry; Spallation; Time-resolved ellipsometry